Single transverse extended incision for radical neck dissection - Chagas,José Francisco Sales (2016)
ABSTRACT Objective: to assess the efficacy of the single transverse extended cervical incision in radical neck dissection. Method: we conducted a prospective study, from January 2008 to January 2009, with 18 patients undergoing surgical treatment of malignant tumors of the upper aero-digestive tract. The primary lesion was located in the oral cavity in eight cases, in the oropharynx in three, in the hypopharynx in three, in the larynx in two, in the maxillary sinus, and in one case, the primary injury was hidden. There were 29 neck dissections, eight bilateral and 10 unilateral (26 radical and three selective). Staging revealed nine patients with T4 tumor, one T3, six T2, one T1 and one Tx. Five patients were N0, nine N2b, one N2c and three N3. The average number of dissected lymph nodes was 34.25. We performed the neck dissection through a single incision located in the middle neck, coincident with the skinfold, with a length of about 2 to 3 cm behind the anterior edge of the trapezius muscle and 3 to 4 cm from the midline for the unilateral neck dissections. Results: as complications, there were myocutaneous flap necrosis in one patient with prior radiation therapy, one lymphatic fistula, one dehiscence of the tracheostomy, one cervical abscess, one salivary fistula and one suture dehiscence. Conclusions: the single extended incision provides adequate exposure of the neck structures, without compromising surgical time, even in bilateral dissections. It does not compromise the resection of all cervical lymph nodes; it has excellent aesthetic and functional results and is easily associated with other approaches to resection of the primary tumor.